Biomimetic Synthesis of Silver Nanoparticles Using Endosymbiotic Bacterium Inhabiting Euphorbia hirta L. and Their Bactericidal Potential - Baker Syed; Hoovinakola Chinnappa Yashavantha Rao; Mysore Nagalingaswamy Nagendra-Prasad; Ashwini Prasad; Ballagere Puttaraju Harini; Pasha Azmath; Devaraju Rakshith; Sreedharamurthy Satish (Scientifica)
The present investigation aims to evaluate biomimetic synthesis of silver nanoparticles using endophytic bacterium EH 419 inhabiting Euphorbia hirta L. The synthesized nanoparticles were initially confirmed with change in color from the reaction mixture to brown indicating the synthesis of nanoparticles. Further confirmation was achieved with the characteristic absorption peak at 440 nm using UV-Visible spectroscopy. The synthesized silver nanoparticles were subjected to biophysical characterization using hyphenated techniques. The possible role of biomolecules in mediating the synthesis was depicted with FTIR analysis. Further crystalline nature of synthesized nanoparticles was confirmed using X-ray diffraction (XRD) with prominent diffraction peaks at 2θ which can be indexed to the (111), (200), (220), and (311) reflections of face centered cubic structure (fcc) of metallic silver. Transmission electron microscopy (TEM) revealed morphological characteristics of synthesized silver nanoparticles to be polydisperse in nature with size ranging from 10 to 60 nm and different morphological characteristics such as spherical, oval, hexagonal, and cubic shapes. Further silver nanoparticles exhibited bactericidal activity against panel of significant pathogenic bacteria among which Pseudomonas aeruginosa was most sensitive compared to other pathogens. To the best of our knowledge, present study forms first report of bacterial endophyte inhabiting Euphorbia hirta L. in mediating synthesizing silver nanoparticles.